The values of (x,y)=(4,4). In terms of x, the value y(x)=8-x, If the given equation is
and
.
Step-by-step explanation:
The given is,
...............................(1)
...............................(2)
Step:1
Solution can be obtained by Elimination method,
Equation (1) is multiplied by (-1) ( Eqn (1) × -1 )
..............................(3)
Substrate the equation (1) and equation (3),
![-x+y=0](https://tex.z-dn.net/?f=-x%2By%3D0)
![x+y=8](https://tex.z-dn.net/?f=x%2By%3D8)
( - )
![(-x-x)+(y-y)=(0-8)](https://tex.z-dn.net/?f=%28-x-x%29%2B%28y-y%29%3D%280-8%29)
![(-2x)=-8](https://tex.z-dn.net/?f=%28-2x%29%3D-8)
![-2x = -8](https://tex.z-dn.net/?f=-2x%20%3D%20-8)
we can cancel the minus because it is available in both sides,
![2x=8](https://tex.z-dn.net/?f=2x%3D8)
![x = \frac{8}{2}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B8%7D%7B2%7D)
x = 4
From the value of x, Equation (2) becomes,
![x+y=8](https://tex.z-dn.net/?f=x%2By%3D8)
![4+y=8](https://tex.z-dn.net/?f=4%2By%3D8)
(Value of y in terms of x)
Where, x = 4
![y =4](https://tex.z-dn.net/?f=y%20%3D4)
Step:2
Check for solution,
.....................................(2)
Substitute the values of x and y,
4 + 4 = 8
8 = 8
Result:
The values of (x,y)=(4,4). In terms of x, the value y(x)=8-x, where x=4. If the given equation is
and
.